Program Percepatan Penurunan Stunting Di Kota Madiun Sebagai Pemenuhan Hak Atas Kesehatan - Sari, Siska Diana (Fakultas Hukum, Universitas Boyolali, 2024)
Abstract This research examines the program to accelerate stunting reduction in the city of Madiun in 2022. Based on Presidential Regulation Number 72 of 2021 concerning the Acceleration of Integrated Stunting Reduction and the Regulation of the National Population and Family Planning Agency of the Republic of Indonesia Number 12 of 2021 concerning the National Action Plan for the Acceleration of Reducing Stunting Rates Indonesia for 2021-2024, as well as Regulation of the Governor of East Java Province no. 68 of 2001 concerning the Acceleration of Reducing Integrated Stunting in 2021-2024. The method used is a normative-empirical research method with data collection techniques through literature studies, documents and interviews. The data analysis method used is an interactive data analysis technique. The research results are based on statutory regulations in the City of Madiun, which does not yet have a Regional Regulation on PPS, however, in the absence of a Regional Regulation, the City of Madiun has issued a policy on the PPS Program which is contained in the Decree of the Mayor of Madiun Number 440-401.103/165/2022 concerning Amendments to Decrees Mayor of Madiun number 401.103/63/2022 concerning the Formation of the Madiun City PPS Team, then the formation of sub-district and sub-district level decrees numbered SK Mayor of Madiun number 440-401.103/019/2022 and 440-401.103/033/2022. Based on data obtained, the stunting prevalence rate in Madiun City in 2022 was 9.7 percent, this figure is down from 2021 which was recorded at 12.4 percent. Abstrak Penelitian ini mengkaji tentang program percepatan penurunan stunting di kota Madiun tahun 2022. Berdasarkan Peraturan Presiden Nomor 72 Tahun 2021 tentang Percepatan Penurunan stunting terintegrasi dan Peraturan Badan Kependudukan dan Keluarga Berencana Nasional Republik Indonesia Nomor 12 Tahun 2021 tentang Rencana Aksi Nasional Percepatan Penurunan Angka Stunting Indonesia Tahun 2021-2024, serta Peraturan Gubernur Provinsi Jawa Timur no 68 Tahun 2001 tentang Pecepatan Penurunan Stunting Terintegrasi Tahun 2021-2024. Metode yang digunakan adalah metode penelitian normatif-empiris dengan teknik pengumpulan data melalui studi pustaka, dokumen dan wawancara. Metode analisis data yang digunakan adalah teknik analisis data interaktif. Hasil penelitian menunjukkan bahwa pemkot madiun telah melaksanakan program percepatan penurunan stunting dengan berbagai kegiatan, terkait regulasi Kota Madiun belum memiliki Peraturan Daerah tentang stunting, akan tetapi dengan ketiadaannya Peraturan Daerah Kota Madiun telah mengeluarkan kebijakan tentang Program PPS yang tertuang dalam Surat Keputusan Walikota Madiun Nomor 440-401.103/165/2022 tentang Perubahan atas Keputusan Walikota Madiun nomor 401.103/63/2022 tentang Pembentukan Tim PPS Kota Madiun, kemudian dibentuknya SK tingkat Kecamatan dan Kelurahan nomor SK Walikota Madiun nomor 440-401.103/019/2022 dan 440-401.103/033/2022. Berdasarkan perolehan data angka prevalensi stunting di Kota Madiun tahun 2022 sebesar 9,7 persen, angka tersebut turun dari tahun 2021 yang tercatat di angka 12,4 persen